Eddy‐Resolving In Situ Ocean Climatologies of Temperature and Salinity in the Northwest Atlantic Ocean. Issue 1 (3rd January 2019) - Seidov, Dan; Mishonov, Alexey; Reagan, James; Parsons, Rost
Abstract: Circulation patterns and thermohaline fields of the Northwest Atlantic are highly variable in space and time and are strongly impacted by various mesoscale phenomena such as quasi‐stationary frontal zones with sharp gradients, meandering jet‐like currents, vortexes, and filaments. These all contribute to building and maintaining complex large‐scale regional structures of ocean tracers, such as temperature and salinity, which persist over time periods of decades and longer. To reflect the existence of these long‐term mesoscale phenomena and diagnose their changes, a new high‐resolution in situ climatology of the Northwest Atlantic was developed. At its core, this eddy‐resolving climatology, with 1/10° horizontal resolution, reveals a cumulative effect of mesoscale dynamics within the Northwest Atlantic. Additionally, strong agreement exists between this in situ climatology and climatologies derived from high‐resolution satellite data, thus providing a validation of the presence of stochastic periodicity of ocean tracer patterns on decadal timescales. Furthermore, large and very localized multidecadal subsurface heat gains southeast of the Gulf Stream was diagnosed using this new high‐resolution regional climatology. It was demonstrated that the climatic shifts in the wind stress over the Northwest Atlantic may play a leading role in this heat accumulation due to subtropical water heaving through Ekman pumping. It is argued that uncovering many important details of long‐term ocean climate variability from in situ ocean data can only be ascertained through the use of eddy‐resolving climatologies. Plain Language Summary: Historically, the long‐term state of the global ocean, particularly for temperature and salinity, has been derived from in situ observational data and mapped to rather coarse horizontal resolutions of 1° and more recently to 1/4°. Most mesoscale activity, such as the meandering of jet streams, eddies, large vortexes, and filaments, cannot be adequately mapped with such resolutions. Unfortunately, in most places in the World Ocean a better resolution is unattainable due to limited observations. However, in a small number of ocean regions higher‐resolution mapping is now possible. These regions are well sampled and in many cases are extremely important for the ocean and Earth's climate. The Northwest Atlantic is one of these regions. Using a large volume of temperature and salinity data, a new decadally averaged high‐resolution (with 1/10°) ocean climatology was compiled for this region and used, in conjunction with ancillary data, to assess ocean climate change and decadal variability in this region with higher accuracy over the past six decades. Key Points: Northwest Atlantic high‐resolution climatology provides descriptions and helps to explain long‐term regional ocean variability Eddy‐resolving climatology and satellite‐derived data imply stochastic periodicity of ocean climate on decadal timescales